The Relationship between User Interaction and Brand Advocacy in Digital Environments - Renfil, Renfil (Celebes Scholar pg, 2023)
In this work in progress Empreds will analyse how user interaction and frequency of interaction has an influence on brand advocacy specifically within digital contexts, and types of content that encourage this action. As a quantitative study, the research has gathered data from a diverse group of social media users, to assess the user interaction data as an influential factor for brand advocacy by using multiple regression analysis together with ANOVA/ANCOVA. The study objectives show that engagement rate, interaction frequency, visual content value are predictors of brand advocacy, where young people are said to have high advocacy. Thus, these outcomes supplement the existing body of knowledge by detailing how various forms of users’ engagement affect brand recommendations and; providing digressive tactics that may be useful to brands attempting to strengthen their bond with their users through digital marketing. It may also be understood as the need for developing engaging and effective content along with focusing at the young people to improve the online brand promotion.